Find the number of positive integers n ≤ 1 0 0 0 , such that the polynomials F n ( a , b , c ) = a ( b − c ) n + b ( c − a ) n + c ( a − b ) n and F 4 ( a , b , c ) = a ( b − c ) 4 + b ( c − a ) 4 + c ( a − b ) 4 have no common non-constant factors.
Details and assumptions
For n = 1 , we have F 1 = 0 , and hence F 4 ∣ F 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Seriously, that was hard. O_O
Log in to reply
Thanks! We consider the last question free frag, and almost anything goes (within reason). It does vary wildly in difficulty.
The initial substitution is motivated from the setup of the question, and makes the polynomials much easier to deal with.
I like the way you showed F 2 m o d F n . Our way was much more brutal, and worked with the polynomials directly.
Very nice.
An even nicer example, when looking for solutions of F 2 ( a , b , c ) = 0 which are not all the same, is a = 1 5 , b = − 6 , c = 1 . F 2 is homogeneous in a , b , c , so we can assume that c = 1 . The requirement that F 2 ( a , b , 1 ) = 0 can be manipulated to give a b = 8 − ( a + b ) ( a + b ) 2 + ( a + b ) and hence a , b must be solutions of the quadratic 0 = X 2 − λ X + 8 − λ λ 2 + λ = ( X − 2 1 λ ) 2 − 4 1 ( λ − 2 ) 2 λ − 8 λ where λ = a + b . To ensure that both roots are rational, we need λ − 8 λ = u 2 to be the square of a rational. Putting u = 3 gives us the all-integer solution (putting u = 2 gives yours).
Log in to reply
Thanks. That's actually a nice spinoff from the problem.
Log in to reply
Yes, a very nice question! The equation is homogeneous of degree three, so it appears to be an elliptic curve on the projective plane at the first glance. But it is actually rational: there is a singular point ( a : b : c ) = ( 1 : 1 : 1 ) . In other words, if we say a = 1 + k t , b = 1 + t , c = 1 , we get a polynomial of degree three for t . It will have a double root at t = 0 , and the other root will vary with k , giving all (or almost all) rational solutions. This is pretty much equivalent to what Mark H. did.
Observe that F 0 = a + b + c , F 1 = 0 , F 2 = ∑ a ( b − c ) 2 = a 2 ( b + c ) + a ( b 2 + c 2 − 6 b c ) + b c ( b + c ) , and considering F n as a linear recurrence in a − b , b − c , c − a , we get F n = U F n − 2 + V F n − 3 for n ≥ 3 , where U = − ∑ ( a − b ) ( b − c ) = 2 1 ∑ ( a − b ) 2 and V = ∏ ( a − b ) . In particular, F 4 = U F 2 . It's also easy to check that U , F 2 are irreducible in R [ a , b , c ] (although U factors as 2 1 ( a + b ω + c ω 2 ) ( a + b ω 2 + c ω ) , where ω = e 2 π i / 3 , in C ), e.g. by noting that any nontrivial factorization of either into two polynomials would have to have both polynomials linear in each variable; for F 2 , this would imply de g F 2 ≤ 1 + 1 , and for U , this would require e 2 π i / 3 ∈ R . But R [ a , b , c ] is a UFD, so F n , F 4 share a factor iff U ∣ F n or F 2 ∣ F n (or both). First we prove that U ∣ F n iff n ≡ 1 ( m o d 3 ) . Taking our recurrence for { F n } mod U , we get F n ≡ V F n − 3 ( m o d U ) . Yet g cd ( U , V ) = 1 and F 1 = 0 is the only one among F 0 , F 1 , F 2 divisible by U , so the result follows by induction. Next, we show that F 2 ∣ F n iff n ∈ { 1 , 2 , 4 } . The "if" direction is clear; now suppose for contradiction that F 2 ∣ F n for some n ≥ 3 not equal to 4 . Then for reals x , y , z , F n ( x , y , z ) = ∑ x ( y − z ) n = 0 whenever F 2 ( x , y , z ) = ∑ x ( y − z ) 2 = 0 . For convenience, we fix z = 1 and y > 9 0 0 0 , and take x to be the smaller root (from the quadratic formula) 2 ( y + 1 ) − ( y 2 − 6 y + 1 ) − ( y 2 − 6 y + 1 ) 2 − 4 y ( y + 1 ) 2 = − 2 ( y + 1 ) y 2 − 6 y + 1 + ( y − 1 ) y 2 − 1 4 y + 1 of F 2 ( x , y , 1 ) (a standard way to factor out the y − 1 is to write y 2 − 6 y + 1 as ( y + 1 ) 2 − 8 y ). We will derive a contradiction by taking y sufficiently large. Using y + 1 1 = y 1 + O ( y − 2 ) and the binomial expansion 1 − y 2 1 4 y − 1 = 1 − 2 1 y 2 1 4 y − 1 + O ( y − 2 ) , we obtain y − 1 1 − x = 2 ( y + 1 ) y − 3 + y 2 − 1 4 y + 1 = 1 − 2 ( y + 1 ) 1 2 + O ( y − 1 ) = 1 − 6 y − 1 + O ( y − 2 ) whence 1 − x = y − 1 − 6 + 6 y − 1 + O ( y − 1 ) and y − 1 x − y = − 1 − y − 1 1 − x = − 2 + O ( y − 1 ) . Since n is constant, this means $$0 = x + y\left(\frac{1-x}{y-1}\right)^n + \left(\frac{x-y}{y-1}\right)^n $$ is $$(8-y+O(y^{-1})) + y(1-6ny^{-1} + O(y^{-2})) + (-2)^n+O(y^{-1}),$$ which is in turn 8 − 6 n + ( − 2 ) n + O ( y − 1 ) . But 8 − 6 n + ( − 2 ) n is an integer, so this can only hold for y large if ( − 2 ) n = 6 n − 8 ⟹ n ∈ { 1 , 2 , 4 } , contradiction. To finish up, our answer is just the number of positive integers n ≤ 1 0 0 0 not congruent to 1 ( m o d 3 ) and not equal to 2 , i.e. 1 0 0 0 − 3 3 4 − 1 = 6 6 5 .
Very nice solution. The O ( y − 1 ) notation at the end means an unknown function, that has absolute value less than C ( y − 1 ) for some fixed constant C , for all sufficiently large y . This "big O " notation is common in Analysis (the branch of mathematics that rigorously supports Calculus). It is also widely used in other areas of mathematics, as well as in computer science. See Wikipedia page for more: http://en.wikipedia.org/wiki/Big O notation.
Besides the Analysis technique, known as "asymptotic expansion", the proof uses some algebra: the fact that polynomials in several variables form a unique factorization domain.
Let
j
=
b
−
c
,
k
=
c
−
a
. Note that
f
(
a
,
b
,
c
)
∣
F
n
(
a
,
b
,
c
)
⟺
f
(
a
,
j
,
k
)
∣
F
n
(
a
,
j
,
k
)
, where
f
(
x
,
y
,
z
)
is any polynomial over three variables. We shall continue our analysis with
a
,
j
,
k
instead. Plugging these values in the expansion of
F
n
(
a
,
b
,
c
)
, it can be shown that
F
n
(
a
,
j
,
k
)
=
a
(
j
n
+
k
n
+
(
−
1
)
n
(
j
+
k
)
n
)
+
j
k
(
j
n
−
1
−
k
n
−
1
)
Let's try to factorize
F
4
(
a
,
j
,
k
)
. Note that
F
n
(
a
,
j
,
k
)
=
a
(
j
4
+
k
4
+
(
j
+
k
)
4
)
+
j
k
(
j
3
−
k
3
)
It can be shown that
j
4
+
k
4
+
(
j
+
k
)
4
=
2
(
j
2
+
j
k
+
k
2
)
2
. We also know that
j
3
−
k
3
=
(
j
−
k
)
(
j
2
+
j
k
+
k
2
)
. It is now obvious that
j
2
+
j
k
+
k
2
is a factor of
F
4
(
a
,
j
,
k
)
. We can now show that
F
4
(
a
,
j
,
k
)
=
(
j
2
+
j
k
+
k
2
)
(
2
a
(
j
2
+
j
k
+
k
2
)
+
j
k
(
j
−
k
)
)
Note that
2
a
(
j
2
+
j
k
+
k
2
)
+
j
k
(
j
−
k
)
≡
j
k
(
j
−
k
)
(
m
o
d
j
2
+
j
k
+
k
2
)
It then follows that
=
g
cd
(
j
2
+
j
k
+
k
2
,
2
a
(
j
2
+
j
k
+
k
2
)
+
j
k
(
j
−
k
)
)
g
cd
(
j
2
+
j
k
+
k
2
,
j
k
(
j
−
k
)
)
For some
k
=
0
, let's consider the equation
j
k
(
j
−
k
)
=
0
in
j
. Note that the roots of this equation are
j
=
0
and
j
=
k
. However, plugging these values in the polynomial
j
2
+
j
k
+
k
2
, we get
k
2
and
3
k
2
respectively, none of which are zero. Hence,
g
cd
(
j
2
+
j
k
+
k
2
,
j
k
(
j
−
k
)
)
=
1
⟹
g
cd
(
j
2
+
j
k
+
k
2
,
2
a
(
j
2
+
j
k
+
k
2
)
+
j
k
(
j
−
k
)
)
=
1
We thus conclude the two factors of
F
4
(
a
,
j
,
k
)
are co-prime. Thus,
F
n
(
a
,
j
,
k
)
will share some common factors with
F
4
(
a
,
j
,
k
)
iff
j
2
+
j
k
+
k
2
∣
F
n
(
a
,
j
,
k
)
or
2
a
(
j
2
+
j
k
+
k
2
)
+
j
k
(
j
−
k
)
)
∣
F
n
(
a
,
b
,
c
)
.
Let
ω
denote the complex cube root of unity, so
ω
2
+
ω
+
1
=
0
. If we consider the equation
j
2
+
j
k
+
k
2
=
0
as an equation in
k
, we get
k
=
j
ω
and
j
ω
2
as roots. Again, if we consider the equation
2
a
(
j
2
+
j
k
+
k
2
)
+
j
k
(
j
−
k
)
=
0
as an equation in
a
, we get
a
=
2
(
j
2
+
j
k
+
k
2
)
−
j
k
(
j
+
k
)
as a root. By the remainder factor theorem, the above condition will be satisfied iff
F
n
(
a
,
j
,
j
ω
)
=
0
or
F
n
(
2
(
j
2
+
j
k
+
k
2
)
−
j
k
(
j
+
k
)
,
j
,
k
)
=
0
Let's try to investigate the first case. Plugging the values in the expansion of
F
n
(
a
,
j
,
k
)
and using the fact that
ω
2
=
−
ω
−
1
, we can show that
F
n
(
a
,
j
,
j
ω
)
=
j
n
(
a
(
1
+
ω
n
+
ω
2
n
)
+
j
ω
(
1
−
ω
n
−
1
)
)
Now, if
n
≡
0
(
m
o
d
3
)
, using
ω
n
=
1
, we can show that
F
n
(
a
,
j
,
j
ω
)
=
j
n
(
3
a
+
ω
j
(
ω
+
2
)
)
=
0
If
n
≡
1
(
m
o
d
3
)
, using
ω
n
=
ω
, we can show that
F
n
(
a
,
j
,
j
ω
)
=
j
n
(
1
+
ω
−
(
1
+
ω
)
)
=
0
If
n
≡
2
(
m
o
d
3
)
, using
ω
n
=
ω
2
=
−
1
−
ω
, we can show that
F
n
(
a
,
j
,
j
ω
)
=
ω
j
(
1
−
ω
)
=
0
We thus conclude
F
n
(
a
,
j
,
j
ω
)
=
0
if and only if
n
≡
1
(
m
o
d
3
)
. There are
3
3
4
such numbers from
1
to
1
0
0
0
.
Let's investigate the second case, when
F
n
(
2
(
j
2
+
j
k
+
k
2
)
−
j
k
(
j
+
k
)
,
j
,
k
)
=
0
. Plugging these values in the expansion of
F
n
(
a
,
j
,
k
)
, it can be shown that
=
F
n
(
2
(
j
2
+
j
k
+
k
2
)
−
j
k
(
j
+
k
)
)
2
(
j
2
+
j
k
+
k
2
)
j
k
(
k
−
j
)
(
j
n
+
k
n
+
(
−
1
)
n
(
j
+
k
)
n
)
+
j
k
(
j
n
−
1
+
k
n
−
1
)
For
n
=
1
and
n
=
2
, we can manually evaluate
F
n
(
a
,
j
,
k
)
and show that it is equal to
0
in both cases. For
n
>
2
, we write down the binomial expansions of the powers.
Note that
=
2
(
j
2
+
j
k
+
k
2
)
j
k
(
k
−
j
)
(
j
n
+
k
n
+
(
−
1
)
n
(
j
+
k
)
n
)
+
j
k
(
j
n
−
1
+
k
n
−
1
)
−
j
k
2
(
j
2
+
j
k
+
k
2
)
(
j
−
k
)
(
2
(
j
2
+
j
k
+
k
2
)
i
=
0
∑
n
−
2
j
i
k
n
−
2
−
i
−
(
j
n
+
k
n
+
(
−
1
)
n
(
j
+
k
)
n
)
This has to be equal to
0
, so we must have
⟹
(
2
(
j
2
+
j
k
+
k
2
)
i
=
0
∑
n
−
2
j
i
k
n
−
2
−
i
=
j
n
+
k
n
+
(
−
1
)
n
(
j
+
k
)
)
n
(
2
(
j
2
+
j
k
+
k
2
)
i
=
0
∑
n
−
2
j
i
k
n
−
2
−
i
=
(
1
+
(
−
1
)
n
)
j
n
+
(
1
+
(
−
1
)
n
)
k
n
+
(
−
1
)
n
i
=
1
∑
n
−
1
(
i
n
)
j
n
−
i
k
i
where the last step follows from writing the binomial expansion of
(
j
+
k
)
n
. Comparing coefficients of
j
n
and
k
n
, we obtain
1
+
(
−
1
)
n
=
2
⟹
2
∣
n
. Again, comparing the coefficients of
j
k
, we obtain
(
−
1
)
n
(
1
n
)
=
4
⟹
n
=
4
. Of course,
n
=
4
is a trivial solution. Also note that
n
=
4
is included in the count of the first case. Other than that, there are
2
values of
n
satisfying the conditions;
n
=
1
and
n
=
2
. But since
1
≡
1
(
m
o
d
3
)
, this is also included in the count of the first case. Thus the second case produces
1
more distinct solution. The total number of such
n
between
1
and
1
0
0
0
is
3
3
4
+
1
=
3
3
5
. Our desired answer will then be
1
0
0
0
−
3
3
5
=
6
6
5
.
Typo:
Note that
f
(
a
,
b
,
c
)
∣
F
n
(
a
,
b
,
c
)
⟺
f
(
a
,
j
,
k
)
∣
F
n
(
a
,
j
,
k
)
.
Another typo: in the middle I replaced k with y .
Also, please make sure you scroll to the right to see the mathematical expressions properly. :)
Log in to reply
Made some edits, though I'm not sure if I got all the y 's.
I used the array environment to get your equations to display on separate lines, to reduce having to scroll back and forth.
Log in to reply
Thanks sir! I have checked my solution again, and it seems that all the k 's are replaced by y 's. But there seems to be a problem in the line "It then follows that g cd ( ⋯ ". I am not sure if I am the only one experiencing the problem, so here's a screenshot:
Loading...
Problem Loading...
Note Loading...
Set Loading...
Let A = b − c , B = c − a , C = a − b , so we have:
F n = a ⋅ A n + b ⋅ B n + c ⋅ C n .
Suppose A , B , C are roots of the cubic equation X 3 − P X 2 + Q X − R = 0 . This gives us P = A + B + C = 0 , Q = A B + B C + C A and R = A B C . Furthermore, since A , B , C satisfy the said cubic equation, we have (since P = 0 ):
A 3 − P A 2 + Q A − R = 0 ⟹ a A n + 1 = − Q ( a A n − 1 ) + R ( a A n − 2 ) .
Similarly, we have:
b B n + 1 c C n + 1 = − Q ( b B n − 1 ) + R ( b B n − 2 ) = − Q ( c C n − 1 ) + R ( c C n − 2 )
Adding these two equations and the earlier one, we get:
F n + 1 = − Q ⋅ F n − 1 + R ⋅ F n − 2 .
In particular, since F 1 = 0 , we have:
F 4 = − Q F 2 + R F 1 = − Q F 2
It is easy to check that both F 2 and Q are irreducible so it remains to find all polynomials F n which are divisible by Q or F 2 .
−
Let's consider Q first. From the recurrence equation F n + 1 = − Q F n − 1 + R F n − 2 we see that F n + 3 is a multiple of Q if and only if F n is. Hence, it suffices to look at just F 1 , F 2 , F 3 . Since F 1 is the only one out of these three which is divisible by Q , we conclude:
Next up, we need to find all n for which F 2 ∣ F n . We claim that n = 1 , 2 , 4 are the only solutions. To do that, we find rational numbers a , b , c satisfying F 2 ( a , b , c ) = 0 . That was hard, but after some effort, we found:
a = − 3 1 0 , b = 1 4 , c = 1
We claim that F n ( a , b , c ) = 0 for n ≥ 5 . Indeed, suppose F n ( a , b , c ) = 0 . Then:
− 3 1 0 1 3 n + 1 4 ( 3 1 3 ) n + ( − 3 5 2 ) n = 0 .
After some simplification, we obtain:
1 4 + ( − 4 ) n = 1 0 × 3 n − 1 .
It is easy to show that this has no integer solution for n ≥ 5 .
Conclusion
The only F n which share a common factor with F 4 are those where n ≡ 1 ( m o d 3 ) or n = 2 . Hence the answer is 1 0 0 0 − 3 3 4 − 1 = 6 6 5 .